Spiritualiteit in een seculiere tijd: Enkele theoretische kanttekeningen vanuit het werk van Charles Taylor - Bernts, Ton (Religie & Samenleving, 2013)
Charles Taylor’s monumental study on our ‘secular time’ comprehends promising theoretical aspects for current research on ‘new spirituality’. In the article I elaborate this with respect to Taylor’s concept of spirituality. He regards spirituality as a lived experience of fullness, that may spring off different, also non-religious sources, and that is to be characterized by a certain degree of ambivalence. In the article I give three examples how Taylor’s concept of spirituality may contribute to theoretical discussions in the sociology of religion. In the first place, the notion of functional equivalents of religion may be questioned because it conceals the differences between spiritual sources and the historical shifts in the underlying spirituality and the contexts in which it is lived. Secondly, the assumption of a stable demand of religion as part of the religious market theory seems to neglect the diversity of spiritual sources and the possibility of low spiritual or religious needs. Finally, Taylor’s concept of spirituality sheds light on the confusing opposition between religiosity and (new) spirituality.